Como tudo (re) começou: a transição para o segundo filho sob a perspectiva de pais e mães - Machado, Raíssa Ducatti Lino (2021)
This study´s objective is to understand the transition to the birth of a second child considering the parent´s perspective. In order to achieve this goal an interpretive qualitative method was used. The study consists five heterosexual couples, ages ranging from 38 to 45 years old derived from a middle-class social stratus. Clinically relevant themes considering the transition to a second child were mapped and as a result we can highlight: care experiences with the first-born acted as facilitators to some aspects to the transition to a second child to both men and women. Both mothers and fathers show higher levels of tranquility, security and self-trust in their performance regarding practical care in relation to the new baby. However, some aspects differentiate the parental experience of having one child and the experience of having two. One aspect was the challenges caused by the changes in relationship between the parents and the first child during the time preceding the birth of the second child. Another important aspect was the distribution of parental attention between the two children at different ages and needs. It was possible to highlight parent´s concerns regarding equal distribution of attention between the children. We could also highlight parental expectations regarding solidary fraternal bonding expectations and clear satisfaction among parents when it was verified. As such, one is able to contextualize a protective context of support to the construction of fraternal relations. The attribution of positive meanings to maternity and paternity created a scenario of protection to these families. Finally, the passage of time has led to accommodation of the parental transition experiences